Age matters: differences in correlates of self-reported HIV antiretroviral treatment adherence between older and younger Black men who have sex with men living with HIV. Issue 8 (3rd August 2019) - Mutchler, Matt G.; Bogart, Laura M.; Klein, David J.; Wagner, Glenn J.; Klinger, Ian A.; Tyagi, Keshav; McDavitt, Bryce
ABSTRACT: Black men who have sex with men (BMSM) show lower levels of adherence to antiretroviral therapy (ART) for HIV medications than other racial/ethnic groups in the U.S. Yet, little is known about age differences in factors that predict ART adherence among BMSM. We combined data from two surveys of HIV-positive BMSM, resulting in 209 participants (130 aged 18–50 years; 79 aged 50 years or older). Multivariate linear regressions examined associations between baseline characteristics and adherence to HIV medications as well as interactions of baseline characteristics with age. The associations between trust in healthcare and doctor satisfaction ratings with higher adherence were stronger for older vs younger men ( p  < .05); the association between problem drinking and lower adherence was stronger among younger men ( p  < .05). Future research should examine how interventions may address these age-specific factors to improve ART adherence among BMSM living with HIV.